Risiko Terjadinya Limfedema pada Pasien Kanker Payudara yang Mengalami Infeksi Setelah Menjalani Operasi Terkait Usia di Rumah Sakit Dharmais - Dadan Prayogo (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2021)
Lymphedema in breast cancer is a disruption of the lymphatic system causing the accumulation of protein-rich fluid in the interstitial space which causes swelling of the arms, shoulders, neck, or the thoracic area. The aim of this study was to determine the risk of lymphedema in breast cancer patients who experienced an infection after undergoing age-related surgery. This research method is an advanced analysis based on previous master research using a case-control multicenter approach design with a total of 110 subjects. Interviews and measurements have been carried out using a questionnaire. The results of the study showed that breast cancer patients who had an infection after surgery were 3.5 times more likely to develop lymphedema than those who did not have an infection after surgery. Patients aged ≥ 50 years with lymphedema were 1.4 times more likely to develop lymphedema than <50 years. Conclusion, patients who experienced infection after surgery with age ≥ 50 years on the incidence of lymphedema were found to be 75.0% with aOR 1, this means cOR ≠ aOR, so there is an indication as a confounding factor, but statistically there is no significant difference with p value> 0.05. Keywords: Breast Cancer, Infection After Surgery, Lymphedema, Without Lymphedema.